Seroprevalence of Toxoplasma gondii in free-living Amazon River dolphins (Inia geoffrensis) from central Amazon, Brazil - Santos, P. S.; Albuquerque, G. R.; da Silva, V. M. F.; Martin, A. R.; Marvulo, M. F. V.; Souza, S. L. P.; Ragozo, A. M. A. [UNESP]; Nascimento, C. C.; Gennari, S. M.; Dubey, J. P.; Silva, J. C. R. (Elsevier B.V., 2011)
Toxoplasma gondii is an important pathogen in aquatic mammals and its presence in these animals may indicate the water contamination of aquatic environment by oocysts. Serum samples from 95 free-living Amazon River dolphins (Inia geoffrensis) from the Mamiraua Sustainable Development Reserve (RDSM), Tefe, Amazonas, Central Amazon, Brazil were tested for T. gondii antibodies using the modified agglutination test (MAT). Antibodies (MAT >= 25) to T. gondii were found in 82 (86.3%) dolphins with titers of 1:25 in 24, 1:50 in 56, and 1:500 in 2. Results suggest a high level contamination of the aquatic environment of the home range of these animals. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Toxoplasmosis; Diagnosis; Amazon River dolphin; Epidemiology